The Role of Suara Muslim Surabaya Radio in the Developing Da'wa through the Millennial Young Muslim Program - Adhitama, Tias Satria; Pratiwi, Adinda Syani; Maesaroh, Imas (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
Adinda Syani Pratiwi, 2019. The Role of Surabaya Muslim Voice Radio in the Development of Da’wa through the Millennial Young Muslim Program (3M). This study examines the role and journey of Suara Muslim Surabaya radio in the development of da’wa through the Millennial Young Muslim program using descriptive qualitative research. The purpose of this research is to explore the role and journey of Suara Muslim Surabaya Radio in the development of da’wa, especially through its program of Millennial Young Muslims (3M). With program concepts and themes tailored to the wants and needs of millennials, 3M is here as a place for discussion and digging for information, especially for various issues relevant to millennials. This study uses observation, documentation and interviews with 3 informants, namely the program director of Suara Muslim Surabaya, 3M Program Producer and 3M broadcaster. The results showed the role of the Surabaya Muslim voice radio in the development of da’wa through the millennial young Muslim program by providing insight into lifestyle, tips, motivation, inspiration, human interest, and success stories. Discussed in a fun, relaxed, and intimate way, but still with Islamic values ​​with the aim of motivating young listeners to have a more worldly and afterlife spirit of success. Further research is expected to be able to dig deeper into the role of radio in the development of da’wa and the strategies used to attract listeners.